Sammansättningar i Språkrådets nyordslistor: produktivitet och förståelighet - Kołaczek, Natalia (Folia Scandinavica Posnaniensia, 2015)
Compounding seems to be the most productive word formation process in Swedish on the basis of “new words’ lists” (Swedish: nyordslistor) registered by the Language Council of Sweden (Svenska Språkrådet). The subject of the research was the productiveness of compounds and their comprehensibility for the native speakers. The material for the corpus analysis showing the productivity of compounds consisted of 353 compound words from the lists from years 2000 – 2012. With help of a survey where pupils from a secondary school in Tingsryd in Småland were asked to define 17 compounds from “new words’ list” 2008 a conclusion could be drawn that compound words are short-lived, ephemeral constructions. The analysis has shown the big pace of changes that the lexicon undergoes and the linguistic creativity of language users as well as their strong need to create new terms. The results can evoke questions about the effectiveness of communication in relation to the features of new words. The article is based on my unpublished master’s thesis.